Root system development and proline accumulation in sugarcane leaves under aluminum (Al 3+ ) stress - Mantovanini, Luana Jandhy [UNESP]; Silva, Renan Gonçalves da [UNESP]; Silva, Jóice de Oliveira Leite; dos Santos, Thiago Mateus Rosa [UNESP]; dos Santos, Durvalina Maria Mathias [UNESP]; Zingaretti, Sonia Marli (Southern Cross Publishing, 2019)
The potential of sugarcane as a food and bioenergy crop is currently driving the expansion of sugarcane production areas throughout the world. This crop may be constantly subjected to unusual environments such as acid soils with aluminum in toxic form (Al 3+ ), leading to problems in cultivation when the soil is not properly prepared. The aim of this research was to select most tolerant sugarcane genotypes to aluminum toxicity by determining root growth and proline content in the leaves. The experiment employed a factorial that was entirely randomized, with four sugarcane genotypes (CTC-2, CTC-14, RB855453, and RB966928) combined with aluminum concentrations (45, 88, 221, 444, 600, 897, 1000 μmol L -1 ), with three replications. Our results suggest that CTC-2 showed higher tolerance to aluminum, with more biomass accumulation in roots when compared to the other genotypes (descending order of tolerance: CTC-2 > CTC-14 > RB855453 > RB966928). Proline level was clearly different for tested genotypes. CTC-2 showed an increase of 58% in the proline level, while genotype RB855453 showed a 24% increase, but only when the aluminum concentration was 897μmolL -1 .
Keywords: Abiotic stress; Osmoprotector; Roots; Saccharum spp.; Toxicity